A Pilot Study of Human Papillomavirus Detection in Urine Using a Novel Nucleic Acid Amplification Test. (4th February 2021) - Marcus, Jenna Z; Abedin, Yasmin; Pierz, Amanda J; Taveras, Yanille; Sollecito, Christopher C; Parmar, Heta; Burk, Robert D; Castle, Philip E
Abstract: Introduction: Human papillomavirus (HPV) testing is the standard-of-care for cervical cancer screening globally. Urine is a promising alternative to collecting a cervical specimen during a pelvic exam for HPV testing. There are no studies to date of HPV testing of urine using the Xpert HPV test. Methods: We conducted a pilot study of 40 women; 30 women undergoing colposcopy because of a previous abnormality and 10 undergoing routine screening, to evaluate HPV detection in urine by the Xpert HPV test on the GeneXpert platform. Xpert HPV testing of urine was done according to the manufacturer's instructions for testing cervical specimens. These results were compared to a reference of combined results of 2 research HPV genotyping tests conducted on cervical specimens and to repeat Xpert HPV testing of urine. Results: Analytic sensitivity and specificity of Xpert testing of urine for any high-risk HPV versus the cervical sample, categorized as HPV positive if at least 1 test was positive, were 64.3% (95% confidence interval [95%CI]  = 42.1–76.1%) and 100% (97.5%CI = 71.5–100%), respectively. Analytic sensitivity and specificity of Xpert testing of urine for any high-risk HPV versus the cervical sample, categorized as positive if both tests were positive, were 66.7% (95%CI = 44.7–84.4%) and 86.7% (95%CI = 59.5–98.3%), respectively. Kappa values for first vs. second and first vs. third testing of urine by Xpert were 0.89 (95%CI = 0.79–1.00) and 0.90 (95%CI = 0.81–1.00), respectively. Discussion: Given the call for global elimination of cervical cancer and widespread availability of GeneXpert, optimizing Xpert HPV testing of urine may be warranted.